Nocturnal growth hormone and gonadotrophin secretion in growth retarded children with Crohn's disease. Issue 11 (November 1981) - Farthing, M J; Campbell, C A; Walker-Smith, J; Edwards, C R; Rees, L H; Dawson, A M
Abstract : Although impaired growth hormone secretion in response to pharmacological stimuli occurs in some growth retarded children with Crohn's disease, its relationship to past and future th is uncertain. We have therefore determined the growth hormone and gonadotrophin response to the physiological stimulus of sleep by continuous venous sampling in five severely gonadotrophin profiles, the mean plasma hormone concentrations during the first five hours of sleep were determined. In three of the five patients, five hour mean growth hormone levels were reduced (3.8, 5.0, and 8.5 mU/l) compared with levels reported previously in normal short children (10-43 mU/l), although the pulsatile pattern of growth hormone secretion was preserved in all. Nocturnal growth hormone secretion was unrelated to the growth velocities of these children during both pre- and post-treatment assessment periods but a significant correlation was found between growth hormone concentration and a disease activity score (r = 0.79, P less than 0.05), suggesting that growth hormone release by the pituitary was influenced by the severity of the disease. Nocturnal growth hormone secretion was also correlated with gonadotrophin secretion (luteinising hormones, r = 0.99, and follicle stimulating hormone, r = 0.96; p less than 0.01) indicating more extensive hypothalamic-pituitary disturbance. These findings suggest that hypothalamic-pituitary function is depressed in growth retarded children with Crohn's disease, but that abnormalities of growth hormone secretion are unlikely to be directly involved in the growth retardation seen in this condition.